2015
DOI: 10.1016/j.bjan.2013.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia analgésica do bloqueio ecoguiado do plano transverso do abdome – revisão sistemática

Abstract: The TAP have been shown to be an effective technique in colorectal surgery, cesarean section, cholecystectomy, hysterectomy, appendectomy, donor nephrectomy, retropubic prostatectomy, and bariatric surgery. However, the data found in RCT are not conclusive, and as a result, it is necessary to develop new and well designed RCT, with enough statistical power to compare different approaches, drugs, doses, and volumes for the same intervention, aiming to answer the current questions and their effects in the habitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Several studies investigating the efficacy of the transverse plane block in managing postoperative pain in women undergoing caesarean sections have noted pain reduction up to 24 hours after surgery. 19 , 30 , 36–39 Similar to our findings, certain researchers observed changes in the initial hours. For example, Lee’s study reported pain reduction as early as 2 hours post-operation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies investigating the efficacy of the transverse plane block in managing postoperative pain in women undergoing caesarean sections have noted pain reduction up to 24 hours after surgery. 19 , 30 , 36–39 Similar to our findings, certain researchers observed changes in the initial hours. For example, Lee’s study reported pain reduction as early as 2 hours post-operation.…”
Section: Discussionsupporting
confidence: 91%
“…For example, Lee’s study reported pain reduction as early as 2 hours post-operation. 19 , 30 , 36 Canakci et al 18 documented comparable outcomes, identifying statistically significant differences in pain levels 2 hours after the caesarean procedure.…”
Section: Discussionmentioning
confidence: 94%
“…Ripoles et al [10] found in their multicenter review study that TAP block reduces the need for analgesia and VAS in post-operative 24 hours. In our study, we found similar results that TAP block reduces meperidine consumption and reduces VAS after the cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…The blockade of peripheral nerves for analgesia of the abdominal wall after surgery has become more frequent, especially with the development of ultrasound technology. 16 17…”
Section: Introductionmentioning
confidence: 99%
“…15 The blockade of peripheral nerves for analgesia of the abdominal wall after surgery has become more frequent, especially with the development of ultrasound technology. 16,17 Quadratus lumborum (QL) block is a technique used to inject local anesthetic in the posterior abdominal wall around the quadratus lumborum muscle to anesthetize the thoracolumbar nerves. 18 It can provide somatic as well as visceral analgesia due to its paravertebral spread.…”
Section: Introductionmentioning
confidence: 99%